NFC TECHNOLOGY ON INTEGRATED E-KTP FOR HEALTH SERVICE POST IN INDONESIA BASED ANDROID - Rakhman, Shinta Oktaviana; Fajri, Ilham Al (MULTINETICS, 2019)
Integrated Service Post is a form of Community Based Effort implemented by, from and with the community, to empower and provide benefits for the community to provide health services for mothers, infants and toddlers. In the implementation of posyandu activities is still manual often posyandu officers about difficulties in terms of data recording and reporting data such as data posyandu patients are missing, unreadable, not written and not running properly. In this research, the application of integrated posyandu application with technology of field-based (NFC) android-based communication. Utilization of NFC technology allows to e-ktp with the data collection process can be done quickly and precisely. Posyandu application based on this android will also facilitate the officers in doing data recording just by using android smartphone posyandu officers which in addition this application can also be part of the smart city support application Depok.